Influence of biological maturity on the muscular strength of young male and female swimmers - Costa, T.; Murara, P.; Vancini, R. L.; Barbosa de Lira, C. A.; Santos Andrade, M. (Journal of Human Kinetics, 2021)
The present study compared the evolution of strength and muscle mass in swimmers of both sexes across different chronological and biological ages. Seventy-six swimmers (55 males and 21 females) from 10 to 20 years of age underwent evaluations of sexual maturation using the developmental stage of the genitals (G1, G2, G3 G4 and G5) and pubic hair (P1, P2, P3, P4 and P5) (Tanner criteria), lean mass using the dual-energy X-ray absorptiometry method, and isokinetic strength of the knee extensor muscles. Boys did not present a significant difference in strength among G1, G2, and G3 (p > 0.05) nor between 10 and 13 years of age (p > 0.05), although significant differences in strength of the extensor (p = 0.038) muscles of the knee were found between G3 and G4 and between athletes of 10 and 14 years of age (extensor muscles, p = 0.033). Muscle mass was different between G3 and G4 (p = 0.003) and between 10 and 14 years of age (p = 0.020). The mean age of boys in the G4 pubertal stage was 13.7 ± 2.0 years, although from 12 to 16 years of age, boys are typically in the G4 stage. Girls showed no significant differences in strength nor muscle mass among the pubertal stages (p > 0.05). We conclude that by equating boys by chronological age, individuals with different pubertal development levels, muscle mass, and strength levels can be grouped. Therefore, the relationship between the level of pubertal deve-lopment and chronological age seems to be a useful strategy for grouping boys, while grouping girls by chronological age seems adequate for training and competition.